1992
DOI: 10.1203/00006450-199204000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Vasopressin and Atrial Natriuretic Peptide Do Not Alter Ion Transport by Cultured Fetal Distal Lung Epithelium

Abstract: ABSTRAa. Previous studies have shown that i.v. arginine vasopressin (AVP) decreases but does not stop lung fluid secretion in term fetuses not in labor. Although it has been presumed that the response to AVP results from augmented sodium transport, there is controversy whether AVP actually does affect sodium transport in mammalian lung epithelium. To determine if AVP or aldosterone could alone or together augment sodium transport in the perinatal lung, we studied primary cultures of fetal rat distal lung epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…This proposed mechanism is consistent with the observation by Goodman et al (38) that AVP increased dome formation in confluent monolayers of cultured lung epithelial cells from adult rats. Contrary to this view, however, three other groups of investigators found no effect of AVP on the bioelectric properties of respiratory epithelium from fetal and adult rats (14,39) and from mature rabbits (40). These observations support the skepticism expressed in a recent commentary on the possible role of vasopressin in stimulating lung liquid clearance by a sodium-dependent process at birth (41).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This proposed mechanism is consistent with the observation by Goodman et al (38) that AVP increased dome formation in confluent monolayers of cultured lung epithelial cells from adult rats. Contrary to this view, however, three other groups of investigators found no effect of AVP on the bioelectric properties of respiratory epithelium from fetal and adult rats (14,39) and from mature rabbits (40). These observations support the skepticism expressed in a recent commentary on the possible role of vasopressin in stimulating lung liquid clearance by a sodium-dependent process at birth (41).…”
Section: Discussioncontrasting
confidence: 50%
“…In these studies, the inhibitory dose of AVP was sufficient to yield plasma concentrations of the hormone that were at least 10 times greater than those that have been measured in sheep during normal spontaneous labor and delivery (12,13). Moreover, a recent report showed that AVP had no significant effect on the bioelectric properties of confluent monolayers of cultured lung epithelial cells harvested from late-gestation fetal rats (14). Thus, the importance of vasopressin in regulating lung liquid clearance near birth is uncertain.…”
mentioning
confidence: 87%
“…On the other hand, in the lung epithelial cells, although it has been demonstrated that the presence of mineralocorticoid receptors in adult and fetal lungs [32], the impact of aldosterone on ENaC regulation is still controversial. It has been reported that treatment with aldosterone did not affect short-circuit current in alveolar type II cells [33] and did not alter the bioelectric properties in FDLE cells [34]. These results show the possibility of differential regulation of ENaC dependent on the various cell types.…”
Section: Discussionmentioning
confidence: 68%
“…It has been reported that natriuretic peptides at 10 Ϫ11 to 10 Ϫ8 M do not alter Na ϩ transport by cultured fetal distal lung epithelium. 89 Influx experiments indicated that ANP, via guanylate cyclase A receptor-produced cGMP, decreased the amiloride-sensitive component of 22 Na ϩ influx with no changes in the ouabain-sensitive 86 Rb ϩ influx in cultured alveolar type II cells. 90 These findings were taken to indicate a preferential extrusion of cGMP on the basolateral membrane and inhibition of amiloride-sensitive Na ϩ channels.…”
Section: Sodium Transportmentioning
confidence: 98%